2008
DOI: 10.3928/01913913-20080901-12
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Retinopathy of Prematurity in a Tertiary Care Newborn Unit in Turkey: Frequency, Outcomes, and Risk Factor Analysis

Abstract: Although frequency of ROP in Turkey is similar to that in the United States, the rate of severe ROP necessitating treatment seems to be higher in Turkey. Neonates with a gestational age of 32 weeks or less, a birth weight of less than 1,250 g, sepsis, and oxygen therapy may have a greater risk of developing ROP and screening should be intensified in the presence of these risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
30
1
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 38 publications
8
30
1
3
Order By: Relevance
“…23,24 The two studies conducted in Ankara reported treatment rates of 53% 3 and 16.1%. 4 Variations in rate of severe ROP among NICUs in Turkey are likely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 The two studies conducted in Ankara reported treatment rates of 53% 3 and 16.1%. 4 Variations in rate of severe ROP among NICUs in Turkey are likely.…”
Section: Discussionmentioning
confidence: 99%
“…2 Turkey's Ministry of Health has implemented no guidelines for ROP screening policy, and few data are available on current incidences and risk factors of ROP in Turkey. 3,4 Because of this, some pediatricians follow screening criteria set by the United States or United Kingdom, and some refer all neonates who received supplemental oxygen. The aim of the present study was to explore incidences and risk factors for ROP and to determine the suitability of UK and US screening criteria for detecting treatable ROP in a single nursery located in Adana, Turkey.…”
mentioning
confidence: 99%
“…19 However, no significant difference was found in plasma concentrations between patients with and those without proliferative diabetic retinopathy. 29 Elevated sE-selectin levels have also been described in the context of tumor growth, 16 metastasis, 17,30,31 rheumatoid arthritis, 11 and infection, 22 indicating that E-selectin is involved in a variety of biological functions, including angiogenesis. We are aware that the restricted study design, in which we did not receive authorization for scheduled blood withdrawals for study purposes, led to limitations in the analysis.…”
Section: Discussionmentioning
confidence: 97%
“…The minimum detectable concentration of sE-selectin was 2.12 ng/mL. Information regarding clinical parameters that have been associated with ROP, such as GA, birth weight, oxygen supplementation, respiratory distress syndrome, 20 BPD, sepsis, and cerebral hemorrhage, 21,22 and other parameters was obtained from the medical records of all the children and analyzed. Our study adhered to the tenets of the Declaration of Helsinki and was approved by the ethics committee of the Albert-Ludwigs-University Freiburg, Germany.…”
Section: Methodsmentioning
confidence: 99%
“…Retinopathy of prematurity (ROP) is an abnormal development of the retinal vasculature in premature infants that may cause severe visual loss [1]. It is the major cause of blindness in newborns and accounts for up to 10% of childhood blindness in developed countries.…”
Section: Introductionmentioning
confidence: 99%